Risk Behaviors of SMP-SMA-SMK Students - Olvie Leonita; Ahmad Yamin; Nur Oktavia Hidayati (Universitas Muhammadiyah Semarang, 2020)
Maladaptive behavior among teenagers, such as increased sexual behavior, smoking, alcoholism, and drugs abuse in big cities also in other regencies in Indonesia and if there is no real intervention it can conduct a decrease on the quality of the younger generation successor of the nation. This research aim on knowing overview of students risk behaviors uses quantitative descriptive method with proportionate random sampling involving 290 respondents. The measuring instrument used was Adolescent Exploratory Behaviour and Risk Rating Scale (AEERS). This study was used by univariate analysis. Result showed that students risk behavior have a low-risk behaviors (62.1%), it is also split in high health risk behavior (59.7%) and low prosocial risk behavior (80.7%). It conclude, students have a low risk behavior, but also have high health-risk behavior and low risk towards prosocial behaviour.